Utility of Prognostic Scoring System Based on Histomorphological Parameters in Low-grade Colorectal Carcinoma - Aneesha Asok Kumar; Faseela Kalayam Kulath; Asiq Sideeque; Nisha Thattamparambil Gopalakrishnan; Akhil Chandran (Journal of clinical and diagnostic research, 2023)
Introduction: Colorectal Carcinoma (CRC) is the third most common cancer worldwide. Percentage of gland formation is the only valid parameter for histologic grading of CRC . Tumour budding and Tumour-infiltrating Lymphocytes (TILs) are emerging prognostic factors in CRC. In recent years high grade CRC has become subject to more precise molecular grading strategies. However low grade cases show in homogenous outcome due to still insufficient categorization. The focus of this study is to determine whether the combination of amount of gland formation, budding, and TILs will allow us to further characterize large in homogenous group of WHO low-grade cases into prognostically significant subgroups. Aim: To estimate the significance of tumour budding and TILs in low-grade CRC and to categorise low-grade CRC into prognostic subgroups taking into account 3 histologic parameters-gland formation, tumour budding and TIL. Materials and Methods: This was a descriptive cross-sectional study done in the Department of Pathology, MES Medical College, Malappuram, Kerala, India. It was an ambispective study (retrospective from January 2015 to December 2021 and prospective from December 2021 to March 2022) which analysed 105 World Health Organization (WHO) low-grade CRC cases. The demographic data of the patients was collected and histopathological assessment of tumour grade, pT, pN, lymphovascular invasion (LVI), Tumour-infiltrating lymphocytes (TIL) and tumour budding (TB) was done on Haematoxylin and Eosin (H&E) stained sections. A morphology-based risk score was developed taking into account 3 parameters- percentage of gland formation, budding, and TIL. For each parameter, 1 to 2 points were given, resulting in a sum score, dividing the CRC cases into a low-, an intermediate-, and a high-risk group. Statistical analysis was performed using SPSS 25. The results were expressed as numbers and percentage. Pearson Chi-square test was used to test the relationship. Results: In the present study degree of budding significantly associated with pT stage (p=0.02), pN stage (p=0.042) and LVI (p=0.038). TIL also differed significantly with pT (p=0.001) pN (p=0.042) and LVI (p=0.004). Applying the prognostic scoring to 105 cases, 33 (31.4%) cases showed high score, 30 (28.6%) cases were of intermediate score and 42 (40%) cases showed low score. The 3 groups differs significantly with pT (0.027), pN (0.035) and LVI (0.015). Conclusion: The present study showed combining different morphological parameters of tumour and tumour environment can help to further subdivide CRC into prognostically significant subgroups.